2013
DOI: 10.1136/bcr-2013-009456
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system relapse in a patient with acute promyelocytic leukaemia: does the risk stratification matter?

Abstract: SUMMARYExtramedullary relapse is an uncommon complication of acute promyelocytic leukaemia (APL). The most common site of extramedullary relapse is the central nervous system (CNS), and the majority of CNS relapses occur in patients with high-risk disease in which white blood cell count at presentation is greater than 10×10 3 /μL. The best management of such patients is still controversial. We describe a 47-year-old man with APL who developed two CNS relapses which were diagnosed through the presence of t(15;1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…1 The rates of second primary malignancies (SPMs) in childhood ALL are significantly higher than in the general population.…”
mentioning
confidence: 99%
“…1 The rates of second primary malignancies (SPMs) in childhood ALL are significantly higher than in the general population.…”
mentioning
confidence: 99%
“…This could be related to the poor‐prognosis biology of CD56+ APL blasts, the only poor‐risk factor in this case. Although CNS relapse has been described in high and intermediate relapse risk cases (based on TLC and platelet count) to our knowledge this is the first case report of isolated CNS relapse in an otherwise low‐risk patient who was CD56 positive.…”
Section: Discussionmentioning
confidence: 76%
“…However, with the increasing number of patients exhibiting disease-free-survival, some patients with late relapse have been observed in clinical practice [18], particularly those with CNS relapse; the majority of these patients have FLT3-ITD gene mutations or other high-risk factors, including cerebral hemorrhage, hyperleukocytosis syndrome in the induction period, a high expression of adhesion molecules (CD56) induced by ATRA treatment, and the bcr3 subtype of the PML/Rara fusion gene [19][20][21]. However, compared with the number of patients with APL exhibiting CR and long-term survival, the number of patients experiencing relapse is almost negligible.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, previous studies have reported that arsenic can penetrate the blood-brain-barrier on its own [25,26], although at a very low concentration [20]; the ratio of CSF/ plasma arsenic concentration has been shown to be 10-20%, with substantial diferences observed among individuals [27]. Some researchers have reported high concentrations of arsenic and diferentiation-syndrome-like phenomena in the CSF of patients, particularly in those with a history of irradiation treatment [28,29].…”
Section: Discussionmentioning
confidence: 99%